1993
DOI: 10.1002/pola.1993.080311202
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic polyesterification in organic media. II. Enzyme‐catalyzed synthesis of lateral‐substituted aliphatic polyesters and copolyesters

Abstract: Enzymatic polymerization of hydroxyesters in organic media has been the subject of a previous and ongoing research in our laboratory. As part of that study, four ϵ‐substituted‐ϵ‐hydroxyesters were synthesized, and then polymerized using crude porcine pancreatic lipase (PPL) in n‐hexane. These lateral‐substituted hydroxyesters polymerized enantioselectively to produce optically active oligomers and a resolved optically active unreacted monomer. It was found that with increasing bulkiness of the lateral substitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 6 publications
0
21
0
1
Order By: Relevance
“…The enantioselectivity increased as a function of bulkiness of the monomer substituent. [145] Lipase Catalyst for Green Polymer Chemistry…”
Section: Polycondensation Of Oxyacids or Their Estersmentioning
confidence: 99%
“…The enantioselectivity increased as a function of bulkiness of the monomer substituent. [145] Lipase Catalyst for Green Polymer Chemistry…”
Section: Polycondensation Of Oxyacids or Their Estersmentioning
confidence: 99%
“…Examples are the first in vitro synthesis of cellulose by cellulase-catalyzed polymerization of b-cellobiosyl fluoride via a non-biosynthetic path way 5) , the first synthesis of chitin via chitinase-catalyzed polymerization of a chitobiose oxazoline derivative 6) , and a new class of polyphenols by peroxidase-catalyzed oxidative polymerization of various phenol derivatives 7,8) . Recently, enzymatic syntheses of aliphatic polyesters have been studied extensively 1,[8][9][10] . Medium-size lactones (6-and 7-membered) as well as macrocyclic lactones (12-, 13-, and 16-membered) were polymerized with a lipase as a catalyst under mild reaction conditions, yielding the corresponding polyesters [11][12][13][14][15][16][17][18][19][20][21][22] .…”
Section: Introductionmentioning
confidence: 99%
“…HPLC analysis showed that the (R)-enantiomer possessed higher enzymatic reactivity. Optically active oligomers (DP < 6) were also synthesized from racemic ε-substituted-ε-hydroxy esters using PPL as catalyst [97]. The enantioselectivity increased as a function of bulkiness of the monomer substituent.…”
Section: Methodsmentioning
confidence: 99%